2009
DOI: 10.1128/aem.00020-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Treatment with β-Lactam on Transfer of the bla CTX-M-9 Resistance Gene from Salmonella enterica Serovar Virchow to Escherichia coli in Gnotobiotic Rats

Abstract: The conjugative transfer of the plasmid carrying the bla CTX-M-9 gene from Salmonella enterica serovar Virchow isolated from a chicken farm to a recipient Escherichia coli strain was evaluated in vitro and in axenic rats inoculated with both strains, with or without selective pressure due to therapeutic doses of cefixime. The transfer of the bla CTX-M-9 gene of S. enterica serovar Virchow to E. coli was confirmed in vitro, at a low frequency of 5.9 ؋ 10 ؊8 transconjugants/donors. This transfer rate was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…In comparison to bla TEM and bla CMY genes, the prevalence of bla CTX-M gene in both E. coli and Salmonella from Meghalaya and Assam was found to be lower. Our result is also in corroboration with the report of other workers [ 13 - 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…In comparison to bla TEM and bla CMY genes, the prevalence of bla CTX-M gene in both E. coli and Salmonella from Meghalaya and Assam was found to be lower. Our result is also in corroboration with the report of other workers [ 13 - 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…In other animal models, the intestinal microbiome can be a formidable barrier to the transfer of antimicrobial resistance (Schjørring et al, 2008;Faure et al, 2009;Stecher et al, 2012). However, this study showed that antimicrobial-resistant Salmonella occurred in the absence of administration of a resistant microbiome.…”
Section: Discussionmentioning
confidence: 66%
“…These plasmids often contain other resistances including chloramphenicol, florfenicol, streptomycin, and tetracycline (Winokur et al, 2000;Doublet et al, 2004;Fernández-Alarcón et al, 2011). In nature, Salmonella acquires MDR plasmids from commensals that inhabit the same environment (Winokur et al, 2001;Fricke et al, 2009;McCollister et al, 2016) and its acquisition of antimicrobial resistance is dependent on an abundant, antimicrobial-resistant donor population (Smith, 1975;Schjørring et al, 2008;Faure et al, 2009;Card et al, 2017). How quickly Salmonella acquires plasmids and associated antimicrobial resistances are dependent on the presence and abundance of the plasmid in the intestinal microbiome, rate of plasmid transmission, plasmid stability and fitness cost (Stewart and Levin, 1977;Ponciano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the transfer of bacterial resistance genes of an animal origin to those of a human origin, and vice versa could be biologically plausible. At present, the evaluation and quantification of these genes flow between human and animal bacterial populations are not conducted [ 26 ].…”
Section: Discussionmentioning
confidence: 99%